Neuroticism and emotion regulation through music listening: A meta-analysis. (September 2020) - Miranda, Dave; Blais-Rochette, Camille
Recent research has found that neuroticism (i.e., trait emotional instability) may dispose people to use music listening as a strategy to regulate their emotions. To estimate the magnitude of this relationship, we performed a meta-analysis (random effects model) of the extant 13 correlational studies ( k = 13) for a total of 2641 participants. Results indicated a significant small-to-medium summary effect ( r =.22, 95% CI [0.17, 0.27]) for the positive correlation between neuroticism and emotion regulation through music listening. Furthermore, there was no evidence of significant heterogeneity in effect sizes across studies. Overall, we conclude that the putative effect of neuroticism on musical emotion regulation is relatively moderate. Findings may suggest that people higher in neuroticism are more prone to use music listening as an accessible resource to regulate their negative emotions or manage whatever affects their mood in everyday life.